The pivotal role of inflammatory factors in glaucoma: a systematic review - Bin Lin; Bin Lin; Bin Lin; Bin Lin; Bin Lin; Bin Lin; Dongkan Li; Dongkan Li; Dongkan Li; Dongkan Li; Dongkan Li; Dongkan Li (Frontiers in Immunology)
Glaucoma, a leading cause of irreversible vision loss, is becoming more prevalent with the aging population, burdening patients, families, and society. In the past, the role of inflammatory factors in its pathogenesis was overlooked. This systematic review, based on a PubMed search and strict screening of 61 articles, selected 19 for in-depth analysis. It was found that multiple inflammatory factors like Tumor Necrosis factor alpha (TNF – α), Interleukin-6 (IL-6), and Interleukin-1 (IL–1) are abnormal in glaucoma patients’ intraocular fluid. They impact trabecular meshwork function, damage retinal ganglion cells, and activate the complement system. Other factors such as Vascular Endothelial Growth Factor (VEGF) and Monocyte Chemoattractant Protein-1 (MCP-1) also contribute to the disease process. Based on these findings, emerging therapeutic strategies for glaucoma may include biological agents targeting specific inflammatory mediators, multitarget anti-inflammatory approaches, and personalized interventions guided by inflammatory biomarker profiling. However, critical challenges such as blood-retinal barrier penetration limitations, systemic immunosuppression risks, and technical hurdles in gene therapy delivery require further investigation. This systematic review synthesizes current evidence to inform clinical decision-making regarding inflammatory biomarker monitoring while identifying key knowledge gaps in ocular immunomodulation. The findings underscore the necessity for translational studies bridging preclinical models with clinical applications, ultimately aiming to optimize therapeutic outcomes for glaucoma patients worldwide.